Idiosyncratic and Systemic Risk in the European Corporate Sector : A CDO Perspective - Lu, Yinqiu (IMF Working Papers; Working Paper, 2006)
Systemic risk remains a major concern to policymakers since widespread defaults in the corporate and financial sectors could pose substantial costs to society. Forward-looking measures and/or indicators of systemic default risk are thus needed to identify potential buildups of vulnerability in advance. In this paper, we explain how to construct idiosyncratic and systemic default risk indicators using the information embedded in single-tranche standardized collateralized debt obligations (STCDOs) referencing credit derivatives indices. As an illustration, both risk indicators are constructed for the European corporate sector using midprice quotes for STCDOs referencing the iTraxx Europe index.